Basal Cell Carcinoma with Disseminated Bone Metastization: An Unusual Outcome of the Most Common Malignancy - Rolim,Luísa (2021)
ABSTRACT Basal cell carcinoma is the most common skin cancer, with a very low incidence of metastases, associated with high morbidity and mortality. The morpheaform clinical variant is uncommon, presenting an aggressive growth pattern. Early diagnosis and new targeted therapies for metastatic disease are important to improve survival rates. We present the case of a 29-year-old patient with morpheaform basal cell carcinoma in the right genian region. Due to local recurrences, he underwent surgery and adjuvant radiotherapy. For extensive metastatic bone involvement, the patient started vismodegib and, later, pembrolizumab, and also performed palliative radiotherapy. Despite several lines of systemic therapy, the disease progressed, and the patient died after 8 years of follow-up. This case shows how crucial it is to identify risk factors for metastatic basal cell carcinoma and highlights the need to improve target therapies and tailor them to the patient’s biological profile.